Al-Nukkarî, "l’Homme à l’âne" qui ﬁt trembler la dynastie fatimide - Ben Mansour, Seyfeddine (2015)
Keywords: Nukkarisme

ثورة أبو يزيد مخلد بن كيداد النكاري بين الأنصاف والتجريح - عشي, علي (İslami İlimler Dergisi, 2015)
Along history the Islamic Maghreb has withnessed a great deal of social, political and ideological revolutions which have caused the region to gain a dynamic structure. These events deeply influenced the whole region, specially the Middle Maghreb.. As one of these important events the uprising of Muhalled b. Yezid has been a quite clear expression of reactions given to the Fatimid politics which are blamed to be sectarian and economically authoritarian. In this article, the reader will find a comparison between Muhalled’s sect and the other sects of the region, the reason why Muhalled asked the help of Omayyad Dynasty, how he found supporters for his mission, how his uprising has expanded over the whole East Africa and an investigation Fatimid politics of the Middle Maghreb. All of teh Arabic, Fatimid and Ibadhi sources will be taken into consideration.
Keywords: Nukkarisme

Aqwāl Qatāda and the Shuʿaybiyya and Nukkār - Madelung, Wilferd (Ibadi jurisprudence: origins, developments and cases, 2015)
Keywords: Nukkarisme